ChemInform Abstract: Access to β‐Lactams by Enantioselective Palladium(0)‐Catalyzed C(sp3)—H Alkylation. Issue 48 (2nd December 2014) - Pedroni, Julia; Boghi, Michele; Saget, Tanguy; Cramer, Nicolai
Abstract This method exhibits a palladium‐catalyzed C—H functionalization for the challenging asymmetric formation of saturated C(sp3)—C(sp3) bonds via a strain‐building reductive elimination resulting in the formation of the four‐membered ring of β‐lactams.